2008
DOI: 10.1103/physreve.78.026202
|View full text |Cite
|
Sign up to set email alerts
|

Interface-selected waves and their influence on wave competition

Abstract: In this paper we study nonlinear oscillatory systems consisting of two media, one supporting forward propagating waves and the other inwardly propagating waves, separated by an interface. We find that the interface can select the type of wave. Under certain well-defined parameter condition, these waves propagate in two different media with the same frequency and same wave number; the interface of the two media is transparent to these waves. The frequency and wave number of these interface-selected waves (ISWs)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
(33 reference statements)
3
19
0
Order By: Relevance
“…These theoretical results are in agreement with the statements made in Ref. [29] and further confirmed by numerical simulations shown in Fig. 6.…”
Section: Ingoing and Outgoing Target Waves In The Complex Ginzburg-lasupporting
confidence: 95%
See 1 more Smart Citation
“…These theoretical results are in agreement with the statements made in Ref. [29] and further confirmed by numerical simulations shown in Fig. 6.…”
Section: Ingoing and Outgoing Target Waves In The Complex Ginzburg-lasupporting
confidence: 95%
“…The criteria or the frequency condition that either ingoing or outgoing target waves are fulfilled is in agreement with the one obtained numerically in Ref. [29]. However, it is deserve emphasizing that the criteria [i.e., Eqs.…”
Section: Ingoing and Outgoing Target Waves In The Complex Ginzburg-lasupporting
confidence: 75%
“…They found that the probability of knotting increased with the length of the string, but plateaued at a value below 100%. 19 Abadie and Dayantis 20 used a lattice representation of random and self-avoiding walks and found that the conformational properties as a function of reduced box size, L/R ee , where L is the edge length of the cube and R ee is the square-root of the mean-squared end-to-end distance of an unconfined polymer chain, were independent of chain length N. 20 Cui et al 21 also used a lattice model of polymers confined in cubes to study the rotational relaxation time T and the looping time for chain ends to meet. At low to moderate confinements, they found that the scaled dynamics s/s 0 $ (L/R ee ) 2 were also independent of N. Here, s 0 $ N 112v is the timescale for an unconfined polymer to diffuse a distance equal to its size, and v describes the variation of an unconfined polymer with the degree of polymerization N, via R ee $ N v .…”
mentioning
confidence: 99%
“…Currently, considerable attention has been paid to a particular kind of nonuniform system that is in the presence of an interface [13][14][15][16]. For instance, it has been reported that negative refraction could occur if chemical waves propagated across the interface in nonlinear oscillatory systems [14].…”
mentioning
confidence: 99%
“…What is more, the authors in ref. [15] observed the interface selected traveling waves, which propagated in two different media with the same frequency and same wave number. The role of interface selected waves in wave competition in two-dimensional (2D) systems was discussed, however the studies in ref.…”
mentioning
confidence: 99%